PENGARUH TEKNIK PENCAHAYAAN ALAMI DAN BUATAN TERHADAP PERSEPSI KESAKRALAN PENGGUNA DI RUANG IBADAH GEREJA SANTO MATIAS RASUL KOSAMBI, JAKARTA - Rosa; Ani Mandala, Ari (Riset Arsitektur (RISA), 2024)
Abstract - As one of the main design elements in sacred spaces, natural and artificial light, plays an important role in responding to the issue of the reduced sacredness of the modern Catholic Church. Santo Matias Rasul Kosambi Church, Jakarta, is a modern Catholic Church designed using natural and artificial lighting techniques. This study aims to determine the effect of differences in natural and artificial lighting techniques during morning and evening worship on the user’s perception of sacredness in the worship room of the Church of Santo Matias Rasul Kosambi, Jakarta. The research was conducted using an qualitative approach (physical observation of the worship space, shape, zone and circulation, enclosing elements and space fillers) and quantitative data (dimensions and proportions of space) and photometric measurements of light (illumination level and luminance)). Aftab Alfa software was used to help display the contrast comparison of the overall church space. The questionnaire was conducted to take the user's perception of the appearance of the room in the morning and evening with natural and artificial lighting which was carried out in a virtual reality room display with 360⁰ photo visualization. The analysis was used to develop the role of lighting techniques used in church rooms in awakening the sacredness of space. Quantitative analysis was carried out by processing the perception data of the questionnaire results using the JMP Pro data processing software. The clarity of the symbolization and ornamentation in the altar area and the clarity of the flow of space in the morning worship has a better value than at night worship. However, night worship is still considered more sacred because of the size and monumental scale of space, clarity of the hierarchy of worship space, and emotion, the value at night worship is higher than during morning worship. The perception that most influences the assessment of the sacredness of the worship space is the size and monumental scale of the space, as well as indicators of the emotions felt in the space, especially positive emotions in the worship space. The clarity of the spatial hierarchy also influences the emotions of admiration, hope, joy, and peace. Keywords: lighting technique, Catholic Church, perception of sacredness, Saint Matias Kosambi Jakarta